Outer Membrane Vesicles as Mediators of Plant–Bacterial Interactions - Rudnicka, Małgorzata; Noszczyńska, Magdalena; Malicka, Monika; Kasperkiewicz, Katarzyna; Pawlik, Małgorzata; Piotrowska-Seget, Zofia (Frontiers in Microbiology, 2022)
Plants have co-evolved with diverse microorganisms that have developed different mechanisms of direct and indirect interactions with their host. Recently, greater attention has been paid to a direct “message” delivery pathway from bacteria to plants, mediated by the outer membrane vesicles (OMVs). OMVs produced by Gram-negative bacteria play significant roles in multiple interactions with other bacteria within the same community, the environment, and colonized hosts. The combined forces of innovative technologies and experience in the area of plant–bacterial interactions have put pressure on a detailed examination of the OMVs composition, the routes of their delivery to plant cells, and their significance in pathogenesis, protection, and plant growth promotion. This review synthesizes the available knowledge on OMVs in the context of possible mechanisms of interactions between OMVs, bacteria, and plant cells. OMVs are considered to be potential stimulators of the plant immune system, holding potential for application in plant bioprotection.